An Autonomous EU Functionality Doctrine for Shape Exclusions. Issue 6 (3rd May 2020) - Suthersanen, Uma; Mimler, Marc D
Abstract: Exclusionary subject matter are often underpinned by public interest considerations. In the case of shapes of products, the Court of Justice of the European Union has aligned the interpretation of the relevant exclusionary provisions within design and trade mark laws. More recently, European jurisprudence within copyright law in relation to conditions of protection has imported the same considerations so as to regulate the protection of shapes of products. This article explores the multitude of doctrinal and policy reasons underpinning shape exclusions and argues that the Court is consciously creating an EU autonomous functionality doctrine within intellectual property law. We also argue that the Court is building a European macro-rationale within these laws namely to ensure that protection does not unduly restrict market freedom and competition.